2016
DOI: 10.1371/journal.pone.0145184
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of the Activator Protein 1 Transcription Factor Regulates Interleukin-1ß Induction of Interleukin 6 in the Developing Enterocyte

Abstract: The innate immune response is characterized by activation of transcription factors, nuclear factor kappa B and activator protein-1 and their downstream targets, the pro-inflammatory cytokines including interleukin 1β and interleukin 6. Normal development of this response in the intestine is critical to survival of the human neonate and delays can cause the onset of devastating inflammatory diseases such as necrotizing enterocolitis. Previous studies have addressed the role of nuclear factor kappa B in the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…TNF-α is an important nuclear transcriptional regulation factor in the body, which is transduced into the nucleus under the induction of a variety of stressors, such as infection and diarrhea, mediates multiple signaling transduction pathways, such as NF-κB, PI3K, Fas/FasL and MAPK, regulates a variety of genes, such as ILs, γ-IFN and VEGF, and participates in inflammatory response, oxidative stress, immune response, embryonic development, cell proliferation, differentiation and apoptosis ( 9 , 10 ). IL-6 is an important pro-inflammatory mediator of the body and a pro-inflammatory factor of many other inflammatory cells and inflammatory media, which is one of the key factors leading to the inflammatory cascade and balance disorder ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α is an important nuclear transcriptional regulation factor in the body, which is transduced into the nucleus under the induction of a variety of stressors, such as infection and diarrhea, mediates multiple signaling transduction pathways, such as NF-κB, PI3K, Fas/FasL and MAPK, regulates a variety of genes, such as ILs, γ-IFN and VEGF, and participates in inflammatory response, oxidative stress, immune response, embryonic development, cell proliferation, differentiation and apoptosis ( 9 , 10 ). IL-6 is an important pro-inflammatory mediator of the body and a pro-inflammatory factor of many other inflammatory cells and inflammatory media, which is one of the key factors leading to the inflammatory cascade and balance disorder ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that AP-1 is a specific nuclear transcriptional factor for IL-1␤-induced IL-6 secretion but only in immature enterocytes (9). AP-1 is composed of c-Jun and c-Fos which are phosphorylated in their active form.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Similarly, other signaling factors connecting TLR4 to nuclear factor-κB (NF-κB) and activator protein transcription factor–mediated inflammation were found to be up-regulated as well, whereas genes that inhibited these signaling pathways were down-regulated. 11 , 16 Together this evidence suggests that an exaggerated innate immune response to colonizing commensal bacteria mediated by TLR activation is mounted by immature intestinal epithelial cells, which could contribute to the pathogenesis of NEC.…”
mentioning
confidence: 95%